IMPROVING VOCABULARY ABILITY BY USING GAME APPLICATION (COC) - Aminatuz Zuhriyah (Program Studi Ilmu Komunikasi, 2017)
The problems of this research were how to improve vocabulary using game application (COC) andhow to motivate the students to apply it in their d English. The research was guided by a conceptualframework leading to the using game aplication through peer work to improve their motivation to speakEnglish during the process of classroom communication interaction. The research type was an actionresearch. The subject consisted of 20 students of the third grade of Islamic Elementary School DarutTaqwa in 2016-2017 academic years. The research data were collected using test (test after first treatmentand test after the second treatment), observation for collecting data on the students’ motivation inimproving vocabulary ability using series pictures. The Data on vocabulary ability using game application(COC) were analyzed using the descriptive and statistic analysis, to know the improvement in meanstudents after the first cycle and the second cycle. Based on the first cycle, the students’ average was 67.8,then, on the second treatment, the students’ average increase to be 78.8. It can conclude that teachingvocabulary using game application can improve students’ vocabulary ability.